The Impacts of Changes in Land Use and Buildings in Baghdad City: Perspectives on Cognitive Dimensions - Al-Jumaily, Saad Khudhair; Tahseen, Eman (International Journal of Environment, Engineering & Education, 2020)
The research aims to study this phenomenon for one of the vital streets of the Baghdad city center to verify the psychological, aesthetic and health dimensions, visual and environmental pollution as cognitive outputs of the phenomenon of the spread of health services and transform the streets from vital whole streets to health centers with a single use. Primary research data obtained using a questionnaire as an instrument consisting of 25 questions addressed to 20 people who have been determined according to the expertise and objects of the study. The object of research is the use of land and buildings on Al-Kindi Street in Al-Harithiya, Baghdad City. It popped up in Iraqi cities emerged because of the deterioration of the security situation, the phenomenon of changing land uses from residential to commercial, and some of them have turned into health uses in the form of individual buildings and complexes in city centers, modern urban centers, and commercial streets. Which caused distortions in the urban scene because of the lack of controls regulating these uses and contributed to the mixing of patients with citizens using these places. A difference found in the evaluation of cognitive outputs of the phenomenon of changing street uses, where the psychological dimensions got 85 percent, the health dimensions 90 percent, and the aesthetic dimensions got 40 percent. These results illustrate the dangerous dimensions of this phenomenon on the behavior and health of citizens and society.